Seed germination dynamics of Carum carvi L. under different temperature regimes and growth regulators - Anand, S B; Priyanka, S; Shweta, B K; Uday, B P; Bijendra, L (Plant Science Today, 2026)
Seed germination is a crucial stage in the crop life cycle. Laboratory experiments were carried out to assess the germination performance of Carum carvi L. seeds and to evaluate the effects of different temperatures and plant growth regulators on their germination behaviour. The present investigation consisted of fifteen treatment combinations, including 3 temperature levels (15, 20 and 25 °C) and 4 concentrations (25, 50, 75 and 100 ppm) of 3 chemical treatments, i.e., Gibberellic Acid (GA₃), Naphthalene Acetic Acid (NAA) and thiourea, arranged in a factorial completely randomized design (CRD). Various germination and growth parameters were recorded during the study and the results revealed that among the different treatment combinations, 20 °C combined with thiourea at 100 ppm was the most effective in enhancing all germination-related traits. The temperature of 15 °C was also found suitable, showing germination performance nearly comparable to that observed at 20 °C. Initial germination was observed after 3 days, with a mean daily germination (MDG) rate of 0.43 seeds day-1, total germination of 65.33 %, germination energy (GE) of 22 %, speed of germination of 1.16 seeds day-1, shoot length (SL) of 5.21 cm, root length (RL) of 3.50 cm and a correspondingly higher seedling vigour index (SVI). However, further studies are required to determine whether increasing thiourea concentration would exert a positive or negative influence on germination. Overall, the treatment combination of 20 °C × thiourea at the rate of 100 ppm was the most effective in enhancing seed germination performance of C. carvi.